Historic buildings, conservation and shifts in social value at Old Umtali: Contestations of heritage in Zimbabwe - Chipangura, Njabulo (University of the Western Cape, 2016)
Magister Artium - MA === The mini-thesis will examine the conservation of colonial historic buildings at Old Umtali (today Mutare) in Zimbabwe and the changes that have affected the buildings in terms of use and maintenance of their architectural character. There has been a shift in heritage management priorities in Zimbabwe and all heritage linked to colonialism has been supplanted by archaeological and liberation war heritage. The result is that the category of colonial heritage which includes historic buildings, forts and memorials have been neglected and vandalised. Various international frameworks in the conservation of buildings will be referred to in this research in examining related questions of urban heritage management. The dichotomy that exists between conservation and adaptive reuse of historic buildings as these issues have unfolded at Old Umtali, a former colonial town with historic buildings constructed in 1891 will be at the centre of this interrogation. Notwithstanding the changes in heritage management priorities in Zimbabwe, the irony is that heritage practitioners are still obliged to conserve historic buildings by legislation. This work then attempts to place back the question of conserving historic buildings on the conservation agenda for a post-colonial Zimbabwe. I argue that historic buildings should be conserved and used for different contemporary purposes and at the same time becoming the subject of interpretative work. Questions can then be asked about the experience of colonialism and the various movements of the Pioneer Column in Zimbabwe using the case study of Old Umtali. In this thesis conservation of historic buildings is not just a technical question but is also seen as an intellectual, epistemological and political question.